An Evaluation of Institutional Matrices Theory Which Was Designed to Illustrate Differences Between Russian and Western Political Economies - Hayden, F. Gregory (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
This article is devoted to the evaluation of the institutional matrices theory (IMT), which was designed to illustrate the differences between Russian and Western political economic systems. IMT has no matrix, and it is an ideological declaration rather than a theory. It is a set of assertions and assumptions that are adopted without evidence, and then hypostatized to be Russian and Western socioeconomic systems. IMT literature claims to utilize the reciprocity, redistribution, and exchange model of Karl Polanyi (1944, 1957). However, IMT suffers from a number of assumptive and methodological problems in its application, the first of which consists of the complete exclusion of reciprocity from consideration. The first section of the article is an explanation of problems with IMT, and the second section demonstrates some particulars of the IMT problems with a real-world social fabric matrix from a Western nation.
Keywords: Russia; economic policy; economics; institutional economics; institutional matrices theory; social fabric matrix; socioeconomics

Strengthening Karl Polanyi’s Concepts of Reciprocity, Double Movement, and Freedom with the Assistance of Abductive Logic - Hayden, F. Gregory (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
My purpose here is to strengthen Karl Polanyi’s work through critique of and extension to abductive processes. Polanyi presented history woven into a new paradigm for analysis of socioeconomic systems, demonstrated discovery similar to abductive processes, and extended abduction into a holistic context. One of Polanyi’s most important contributions to socioeconomic analysis is the explanation of three integrated network models of socioeconomic reciprocity. They are coadjuvancy, redistribution, and market exchange. Polanyi extended abductive reasoning in two ways. First, he extended it beyond the cognitive logic of a person to inferences and societal belief changes of institutions. Second, he showed that, in the real world, beliefs are not only fixed like an abductive process, they are fixed in law. Throughout Polanyi’s historical presentation, market beliefs are being revised, thus serving as a demonstration of the abductive process. I make both positive and negative critique of a number of Polanyi’s concepts, with special attention to reciprocity, the double movement, and freedom. This critique and abduction extension strengthens Polanyi’s paradigm for future socioeconomic analysis with his integrative network models.
Keywords: abductive logic; beliefs; double movement; economic theory; freedom; production; reciprocity; reciprocity (commerce); socioeconomic; socioeconomics; stock exchanges